Venture capital financing in Ghana: "challenges and prospects" - Anokye-Yeboah, William (2014)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirement for the award of Master of Business Administration (Banking and Finance)